Pt-bridges in various single-strand and double-helix DNA sequences. DFT and MP2 study of the cisplatin coordination with guanine, adenine, and cytosine - Pavelka, Matej; Burda, Jaroslav V (Journal of molecular modeling, 2007)
In this study, various platinum cross-links in DNA bases were explored. Some of these structures occur in many cis/trans-platinated double-helixes or single-stranded adducts. However, in the models studied, no steric hindrance from sugar-phosphate backbone or other surroundings is considered. Such restrictions can change the bonding picture partially but hopefully the basic energy characteristics will not be changed substantially. The optimization of the structures explored was performed at the DFT level with the B3LYP functional and the 6-31G(d) basis set. Perturbation theory at the MP2/6-31++G(2df,2pd) level was used for the single-point energy and 6-31+G(d) basis set for the electron-property analyses. It was found that the most stable structures are the diguanine complexes followed by guanine-cytosine Pt-cross-links, ca 5 kcal mol(-1) less stable. The adenine-containing complexes are about 15 kcal mol(-1) below the stability of diguanine structures. This stability order was also confirmed by the BE of Pt-N bonds. For a detailed view on dative and electrostatic contributions to Pt-N bonds, Natural Population Analysis, determination of electrostatic potentials, and canonical Molecular Orbitals description of the examined systems were used.
Keywords: adenin; cisplatina; jednovláknová DNA; cytosin; Models, Molecular; molekulární modely; heteroduplexy nukleové kyseliny; Cytosine; DNA, Single-Stranded; Platinum; Cisplatin; Nucleic Acid Heteroduplexes; guanin; Adenine; platina; Guanine